Regulatory mechanisms of miR-96 and miR-184 abnormal expressions on otic vesicle development of zebrafish following exposure to β-diketone antibiotics. (January 2019) - Li, Jieyi; Ling, Yuhang; Huang, Wenhao; Sun, Limei; Li, Yanyan; Wang, Caihong; Zhang, Yuhuan; Wang, Xuedong; Dahlgren, Randy A.; Wang, Huili
Abstract: Chronic ototoxicity of β-diketone antibiotics ( DKAs) to zebrafish ( Danio rerio ) was explored in detail by following abnormal expressions of two hearing-related miRNAs. Dose-dependent down-regulation of miR-96 and miR-184 was observed in otoliths during embryonic-larval development. Continuous DKA exposure to 120-hpf larva decreased sensitivity to acoustic stimulation. Development of otolith was delayed in treatment groups, showing unclear boundaries and vacuolization at 72-hpf, and utricular enlargement as well as decreased saccular volume in 96-hpf or latter larval otoliths. If one miRNA was knocked-down and another over-expressed, only a slight influence on morphological development of the otic vesicle occurred, but knocked-down or over-expressed miRNA both significantly affected zebrafish normal development. Injection of miR-96, miR-184 or both micRNA mimics to yolk sac resulted in marked improvement of otic vesicle phenotype. However, hair cell staining showed that only the injected miR-96 mimic restored hair cell numbers after DKA exposure, demonstrating that miR-96 played an important role in otic vesicle development and formation of hearing, while miR-184 was only involved in otic vesicle construction during embryonic development. These observations advance our understanding of hearing loss owing to acute antibiotic exposure and provide theoretical guidance for early intervention and gene therapy for drug-induced diseases. Graphical abstract: Image 1 Highlights: miR-96 and -184 down-regulation following DKA exposure during embryonic development. miR-96 play a critical role in otic vesicle development and formation of hearing. miR-96 influences otic vesicle development by affecting hair cell differentiation. miR-184 is involved in otic vesicle construction during embryonic development.